Calon Presiden dan Wakil Presiden Independen: Studi Perbandingan dan Tawaran Implementasinya di Indonesia - Rilo Pambudi. S (Fakultas Hukum Universitas Bangka Belitung, 2022)
The stagnation of discussions to accommodate independent presidential and vice-presidential candidates may be because an appropriate pattern of implementation has not been found. Therefore, it is important to learn from best practices in other countries. From this comparison, it is hoped that this will be the basis for the idea of implementing it in Indonesia. To discuss this, this paper uses a combination of statute approach, conceptual approach, and comparative approach. The results show, first, that the United States and Egypt are more flexible in managing the nominations for President and Vice President by implementing a multi-track system. Second, there are two implementation models that can be adopted, namely public support and nominations by state institutions. In the Indonesian context, both can be applied with some adjustments because in principle they have been practiced.